Delik Pidana Materiil Penipuan Melalui Media Sosial - Setiawan, Hari; Dj. Sidarta, Dudik (Universitas Ekasakti, 2024)
Fraud is a form of general crime in Indonesia according to the Criminal Code. Social media is also developing rapidly with the development of information flow and technology. However, along with the development of the times and the improvement of information and communication technology, fraud is not only carried out directly through face to face, but also through cyberspace/internet or more trendingly through social media. The forms of fraud through social media that occur are quite diverse, including online arisan, investment, and savings and loans, as the author made the thesis material, namely the decision of the Surabaya District Court regarding the decision of the case court fraud via social media. The main issues taken are how the material offense is against fraud through social media and what are the considerations in deciding cases of fraud through social media in question. The research conducted is normative juridical law research.